2010
DOI: 10.1001/jama.2010.1665
|View full text |Cite
|
Sign up to set email alerts
|

Infection With Transmissible Strains of Pseudomonas aeruginosa and Clinical Outcomes in Adults With Cystic Fibrosis

Abstract: SEUDOMONAS AERUGINOSA IS A gram-negative bacterium that causes chronic endobronchial infections in 60% to 70% of adult patients with cystic fibrosis (CF). 1 Infection with P aeruginosa is associated with increased morbidity and mortality for patients with CF, irrespective of lung function. 2,3 However, there is heterogeneity in the type and timing of outcome among those who are infected with P aeruginosa; some patients experience a rapid decline in pulmonary function after infection and others harbor the organ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
177
2

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 149 publications
(181 citation statements)
references
References 28 publications
2
177
2
Order By: Relevance
“…Because our entire clinic cohort was not assessed (i.e., we excluded those without P. aeruginosa infection), this number overestimates the true measure of incident infections. These low rates of acquisition are in accord with the work of Aaron et al during their 3-year prospective study involving 446 CF adults in Ontario, as they observed an incidence of 7 cases per 1,000 person-years (9).…”
Section: Figsupporting
confidence: 87%
See 4 more Smart Citations
“…Because our entire clinic cohort was not assessed (i.e., we excluded those without P. aeruginosa infection), this number overestimates the true measure of incident infections. These low rates of acquisition are in accord with the work of Aaron et al during their 3-year prospective study involving 446 CF adults in Ontario, as they observed an incidence of 7 cases per 1,000 person-years (9).…”
Section: Figsupporting
confidence: 87%
“…Only strain A (LES), strain B, Houston-1, and now PES have been described to date in North America (9,31,32). The mechanisms by which these strains are capable of being transmitted from one patient to another are poorly understood, but cough aerosol is the most commonly presumed mechanism (16,33).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations